GALILEO'S METHODOLOGICAL VERSATILITY IN THE DEVELOPMENT OF HIS PHYSICS - W. D, Araújo Filho; Ramos, P. A. O (International Journal of Research -GRANTHAALAYAH, 2020)
Galileo's way of doing science is very controversial. Some historians interpret their work in the light of empiricism, that is, science constructed through sensory data interpreted in the light of logical-mathematical reasoning. Others interpret their work under the aegis of rationalism, by means of which science is constructed, a priori, starting from reality, through pure hypothetical-deductive reasoning. In this view, Galilean experimental incursions played a secondary role in the development of his work. Therefore, two distinct forms of interpretation arise and an asymmetric view of doing science. The scientific method is seen as a recipe, and in an attempt to obtain explanations that best approach reality and achieve true knowledge, it is imperative to follow certain pre-established rules or predetermined restrictions. In contrast, sectarian-free interpretations clarify and promote the genesis of Galilean thought, taking it to a much more complex and lavish level. Some interpretations suggest raising the condition of Galileo to genius and not to a great talent, without observing that the difference between them lies in the addition of intuition to talent, an indispensable ingredient for the transposi-tion between the empirical and rational instances at the right time, so natural to geniuses. According to this point of view, Galileo's work challenges the thesis of being an asymmetric and closed process, replacing it with a dialectical bias, giving intuition and imagination essential roles in the development of his work, hence the genius of his work. personality. This work seeks to understand the genesis and motivations inherent to Galileo's works and the impossibility of compartmentalizing his activity, thinking and originality in narrow and imprecise molds.